(3GdKZhQ GdHGSeI aj efGbH GdSjOI aGWeIs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3GdeOjfI GdefhQIs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3CNHQfj TjNj TjN GdESdGe hGdeSdejf Jbj GdOjf GdSefj HbQGAJj Ydjg bGd GfG GdLeGd YHO Gddg Hf Ydj GdMfHdj bGd CfG CHh GdMSf GdYQVj bGd GfHG RjfH HfJ ecj M hCfHGfj YGdjG CHh YHO Gddg (B...s
(3BNQgG (B:s
(3hGdCQV ef HYO GdfHj cFjHI (B* (3CSakG Ydjg cKj`QI GdQLa``Gf (B*** (3adjHcg T`Qb GdHdGO hZQHgG (B* (3hdjHcg eV`lQ hcoqd jeGf``j (B. ... (3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\301s
(3cTa GdXfhf (B1\521s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs